Muscle mass heavily influences creatinine-based renal function estimation: a 12-year longitudinal general population-based cohort study. (25th November 2020) - Groothof, D; Post, A; Polinder-Bos, H.A; Kieneker, L.M; Flores-Guerrero, J.L; Kootstra-Ros, J.E; De Borst, M.H; Gansevoort, R.T; Spycher, B.D; Erler, N.S; Bano, A; Muka, T; et al.
Abstract: : Muscle mass heavily influences creatinine-based renal function estimation: a 12-year longitudinal general population-based cohort study Background: Current guidelines suggest the use of estimated glomerular filtration rate (eGFR) based on creatinine as measurement of renal function. However, the influence of muscle mass as key determinant of creatinine after renal function may render those estimates imprecise. Purpose: To investigate the effects of 24-hour height-indexed creatinine excretion rate (CER index) – deemed an excellent marker of total muscle mass – on creatinine-based eGFR and to compare this with effects of CER index on muscle mass-independent cystatin C-based eGFR. Methods: We included community-dwelling individuals aged 28–75 years enrolled in the prospective Prevention of REnal and Vascular ENd-stage Disease study. CER was assessed in paired 24-h urine specimens collected during five consecutive screening rounds, each round comprising two outpatient visits separated by three weeks. Cross-sectional and longitudinal associations were respectively quantified using linear regression and linear mixed-effects models, both of which were adjusted for sociodemographic and cardiovascular risk factors. Results: Of the 7, 698 individuals aged 49.8 (12.6) years, of whom 3, 839 (49.9%) were male, baseline mean (SD) CER index was 7.0 (1.8) mmol/(24 h·m). Lower CER index was curvilinearly associated with higher creatinine-based eGFR and lower cystatin C-based eGFR (Figure 1). In a hypothetical 70-year-old male, assumed to have a CER index of 4 mmol/(24 h·m) (indicating low muscle mass), predicted creatinine-based eGFR and cystatin C-based eGFR were 79.8 and 64.1 (difference: 15.7) ml/min per 1.73 m 2, respectively (Figure 1). If the CER index is held constant at 4 mmol/(24 h·m), the predicted ages at which the threshold of 60 ml/min per 1.73 m 2 for the detection of chronic kidney disease would have been exceeded, were 84.7 years for creatinine-based eGFR and 72.7 years for cystatin C-based eGFR (difference: 12.0 years) (Figure 1). During 12.5 years of follow-up, CER index decreased with 0.21 (0.23) mmol/(24 h·m) per 10 years. For every 0.1 mmol/(24 h·m) annual decrease in CER index, creatinine-based eGFR increased with 0.16 (0.07 to 0.25; P=0.0004) ml/min per 1.73 m 2 per year, whereas cystatin C-based eGFR decreased with 0.25 (0.15 to 0.34; P<0.0001) ml/min per 1.73 m 2 after full adjustment. Conclusions: Low muscle mass may cause considerable overestimation of single measurements of creatinine-based eGFR compared with cystatin C-based eGFR. Moreover, loss of muscle mass may cause spurious increases in repeatedly measured creatinine-based eGFR. Implementing muscle mass-independent markers for estimating renal function, like cystatin C, could provide a better alternative to accurately assess renal function in all settings wherein low muscle mass or muscle wasting may be encountered. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Dutch Kidney Foundation